2021
DOI: 10.1177/21582440211047572
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Studies on Social Media: A Bibliometric Analysis

Abstract: This study aimed to present the status quo of linguistic studies on social media in the past decade. In particular, it conducted a bibliometric analysis of articles from the field of linguistics of the database of Web of Science Core Collection with the aid of the tool CiteSpace to identify the general characteristics, major strands of linguistics, main research methods, and important research themes in the area of linguistic studies on social media. The main findings are summarized as follows. First, the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…LITERATURE REVIEW As stated earlier, linguistic studies on social media are attracting the attention of researchers in the field. According to Sun et al (2021), the majority of linguistic studies on social media are in the sub-fields of sociolinguistics, discourse analysis, pragmatics, and applied linguistics. It was also found that most studies are conducted on the social media platforms of Twitter and Facebook.…”
Section: The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…LITERATURE REVIEW As stated earlier, linguistic studies on social media are attracting the attention of researchers in the field. According to Sun et al (2021), the majority of linguistic studies on social media are in the sub-fields of sociolinguistics, discourse analysis, pragmatics, and applied linguistics. It was also found that most studies are conducted on the social media platforms of Twitter and Facebook.…”
Section: The Studymentioning
confidence: 99%
“…For instance, the Labovian framework of the interview which elicits casual/careful styles (Labov, 1972) does not work for other languages, e.g., Arabic because it will trigger the use of Standard Arabic rather than different styles (Al-Wer, 2013). As technology advances, it can be observed that sociolinguistic studies relying on social media data are gaining traction (Sun et al, 2021). In this study, the speech of social media influencers in Najd will be analyzed sociolinguistically to further explore the possibility of using it as a reliable data source for Najdi dialects.…”
Section: Introductionmentioning
confidence: 99%
“…Also, all documents including the top 8 documents with the highest score citation were journal articles. It means that the journal article dominates the eight most influential documents [24], [35].…”
Section: B Science Mapping and Network Analysis 1) Citation Analysismentioning
confidence: 99%
“…To date, many bibliometric analysis studies related to foreign language education have been carried out widely by a lot of researchers [20]- [30]. In addition, several bibliometric analysis types of research regarding technology-based English learning such as computer, website-based assessment, e-books, social media, and wearable devices also have been performed by some researchers [31]- [35]. In contrast, this study focuses on exploring and analyzing the large scientific data from the Scopus database regarding technology-based foreign language learning during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the proliferation of open access databases and availability of free software for analyses, it has become the central means for evaluating scholarly publications and their producers. Although bibliometric studies have been primarily used in natural sciences, recently it has also been used in the broad category of social sciences, especially in disciplines like linguistics ( Sun et al, 2021 ), economics ( Samudra, 2023 ), psychology ( Dong et al, 2022 ), and publication media ( Petrovich, 2022 ). This paper aims to extend this method to the discipline of sociology further by putting the work of American social theorist and ethnographer Michael Burawoy to bibliometric analyses.…”
Section: Introductionmentioning
confidence: 99%